Regression of Science Process Skills On Critical Thinking Skills In Two Junior High Schools In Jambi City - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Aziza Putri Ningsi; Dinda Desma Romadona; Retno Wulan Dari (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
This study aims to look at the effect of science process skills on Jambi City Junior High School students' critical thinking ability on the density and reflection of the material in the mirror. This research method used was mixed method, while the design used was sequential explanatory. The study was conducted at Adhyaksa 1 Junior High School in Jambi City and Al-Jauharen Islamic junior high school in Jambi. The sampling technique used was cluster sampling, so that the sample of this study amounted to 58 students. The data collection instrument consisted of an observation sheet of science process skills, a test of critical thinking skills, and an interview. Data were analyzed using descriptive statistics and inferential statistics. Based on the results of the linear regression test that has been carried out, the t value is greater than the t table, it can be said that there is a significant influence between science process skills and critical thinking skills on the density material and the reflection on the mirror. Students who have low process skills will tend to have low critical thinking skills. Low science process skills and students' thinking abilities lead to low student learning outcomes.